Cutback Management during the Great Recession: The Case of Transit Agencies and Contracting Out. (December 2014) - Smirnova, Olga V.; Leland, Suzanne M.
The following study looks at both qualitative and quantitative data collected from surveys of transit agency managers during and after the Great Recession to see if managers report changes in service provision arrangements in response to fiscal pressure. We investigate whether contracting out services is used as a method of cutback management. We find that the majority of agencies are unable to respond to current economic situation by changing service arrangements because of various and sometimes costly constraints such as state law, the level of competition in the bidding process, and length of contracts.